Biomass energy flow screening for good governance in agricultural system: a case study in Terengganu state - Latifah Abdul Ghani, (Penerbit Universiti Kebangsaan Malaysia, 2018)
A good and sustainable governance in agricultural waste management is considered effective by maximising the economic profit, and at the same time minimising the effect of environmental pollution. This paper presents the findings of the flow of biomass energy in the agricultural productivity system in Terengganu by using Material Flow Analysis (MFA) technique with the aid of SubsTance Flow Analysis (STAN) 2.5 software. Simultaneously, a combined focus was also given by studying the governance system of the relevant parties in organising the agricultural waste management. The findings show that the biomass energy flow centred on the crop subsystem with the total energy input of 509 Peta Joule (PJ) per year from which 68 percent was contributed by the pasture community, which was equivalent to 344 PJ per year. Other than that, the livestock subsystem that was dominated by cattle species contributed the highest biomass energy flow of 54 percent which is equivalent to 202 PJ per year. In addition, it was also found that the involvement of governance, especially from the agropreneur, was still unclear and inadequate which indirectly contributes to the zero bioenergy development in this region. It is hoped that the developing of MFA technique with social field performed in this research would be able to highlight several important issues such as current flow and reservoir level in other area.